EARLY ENTERAL INFUSSIONS IN COMPLEX TREATMENT OF SEVERE COMBINED CHEST TRAUMA - A. N. Tulupov; V. M. Luft; G. I. Sinenchenko; A. V. Lapitskiy; S. Sh. Taniya (Вестник хирургии имени И.И. Грекова)
On the basis of study and treatment of 98 victims it was stated that the absorption of isotonic glucose electrolytes solutions in the small intestine was saved even increased in case of large hemorrhage in severe polytrauma with chest, abdominal injury and other regions trauma. An application of early enteral infusions allowed reducing of the volume of parenteral introduction solutions and facilitated to a reliable decrease of development frequency of nosocomial pneumonia of attributive lethality.